Embryonal rhabdomyosarcoma of the cervix presenting as a cervical polyp in a 16-year-old adolescent: a case report - Jayi, Sofia (BioMed Central, 2014)
INTRODUCTION: Embryonal rhabdomyosarcoma of the female genital tract is rare in the cervix. It has been mainly discussed in the context of individual case studies. It tends to occur in children and young women. Treatment ranges from radical surgery to conservative surgery, followed by chemotherapy. CASE PRESENTATION: A 16-year-old Moroccan adolescent girl presented to our center with a protruding mass from her vaginal introitus, as a polyp of 6cm. An examination revealed a polyp within her vagina, thought to be arising from her cervix and a polypectomy was performed. Microscopic findings are consistent with an embryonal rhabdomyosarcoma (botryoide type). A computed tomography of her thorax, abdomen and pelvis were performed and residual disease was found as a mass located at her cervix, which measured approximately 4.5cm in its widest dimensions, without evidence of metastatic disease. Due to the fact that she is young, after discussions in a multidisciplinary meeting, she was subsequently treated with four cycles of multi-agent chemotherapy. Two cycles of chemotherapy and radiotherapy were administered due to the lack of response, but she presented vaginal bleeding with persistence of the same mass in computed tomography. Hence a total interadnexal hysterectomy was made. A histologic examination found residual embryonal rhabdomyosarcoma (botryoide type) located in all her cervix and she is currently under chemotherapy. CONCLUSIONS: The presence of a cervical polyp in an adolescent is a gynecologic oddity and must necessarily be examined histologically because it might be a rhabdomyosarcoma. This is extremely important because diagnosis at an early stage of the disease is a highly favorable prognostic factor that allows “fertility-sparing surgery” for these young patients.